Ijtihad, Pendidikan, dan Politik dalam Pemikiran Muhammad Rasyid Ridha - Adi Rahmat Kurniawan (IAIN Bengkulu, 2021)
The problem of religiosity is one of the themes that characterize the modern era today. This problem was marked by widespread issues of secularization, liberalization and pluralism which triggered reactions from Muslim scientists, such as Muhammad Rasyid Ridha. This text aims to examine Rosyid Ridha's thoughts on the theme of ijtihad, education and politics. By using the analytical descriptive method, this study concludes several important points. First, Rasyid Ridha contributed effectively from all aspects of benefit in the fields of ijtihad, education and politics. He includes religious elements that refer to the Al-Qur'an and Hadith, such as in his teacher Jamaluddin Al-Afghani. Second, he offers a well-known solution, namely by re-buzzing ijtihad. And third, taking modern thinking and then integrating it with Islam without eliminating syari'ah values. In Rida's concept of thought, he always combines Western and Islamic sciences but still prioritizes religion based on the Al-Qur'an and Hadith. Because of this, his thinking is considered to be a solution in facing the modern era today.